Temporary agency work and the great recession - Daniel Baumgarten; Michael Kvasnicka (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2016)
We investigate with German data how the use of temporary agency work has helped establishments to manage the economic and financial crisis in 2008/09. We examine the (regular) workforce development, use of short-time work, and business performance of establishments that made differential use of temporary agency work prior to the crisis. Overall, our results suggest that establishments with a greater use of temporary agency work coped better with the sharp decline in demand and made less frequent use of government-sponsored short-time work schemes.
urn:nbn:de:bvb:19-epub-27991-8
Keywords: E32; J23; L23; J68; 330; labour demand; employment adjustment; economic crisis; temporary agency work; short-time work; establishment data